Excellence in diabetes and endocrinology 2012; September 6-8, 2012, Rocco Forte Hotel, Abu Dhabi, UAE - Beshyah, Salem; Deeb, Asma (Ibnosina Journal of Medicine and Biomedical Sciences, 2012)
This conference is the second of the series of “Excellence in Diabetes and Endocrinology” organized jointly by the adult and pediatric departments of endocrinology at Sheikh Khalifa Medical City and Mafraq Hospitals in Abu Dhai, United Arab Emirates. The organizers are building on the great success of the first meeting held in 2010. The importance of adult and pediatric endocrine physicians is particularly relevant in this part of the world where the transfer of care from pediatrics to adults clinic may occur as early 13 years of age. Practicing adult physicians may find themselves faced by situations they may not have met during their formal training. Several international, regional and national speakers participated in the conference to address most topical issues in diabetes and endocrinology covering global and regional epidemiology, diagnostic strategies, and the latest good clinical care guidelines. The abstracts are grouped under the sub-headings of their respective sessions. We hope by publishing these abstracts we extend the education cause of the conference.
Keywords: Diabetes; Thyroid; Phaeochromycytoma; Disorders of sex differentiation; Growth hormone deficiency; Hypoglycemia; Culturally sensitive care; Cardiovascular protection in diabetes; Vitamin D deficiency in the Middle East.